Rehearsals of Release - Nicholson, Benjamin Ross (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2024)
Dispossession is not only harmful for the material deprivations it instantiates (though these harms are brutal, even genocidal). To the extent that dispossession occurs within a societal context in which possession is the ultimate virtue, dispossession further diminishes the social significance of those dispossessed; beneath a global regime of neoliberalism, to be lacking in possessions is to be rendered non-agential, unworthy of political representation, and, ultimately, subject to premature death for the profit of others. In the United States and other white-dominated nations, the sickness of white supremacy and its coinciding colonial incursions are rooted in liberal notions of property, doctrines of what can be possessed, what significance possession confers, and who is permitted to do the possessing. This possessive individualism benefits those who have longest held the ability to accumulate wealth via dispossession: already-wealthy white men. This social reality has ruinous effects for those whose cultural values are not predicated on possession yet are subject to the hegemonic forces of white supremacy. In this writing, I propose three “rehearsals of release,” replicable and mutational performances, that can be practically implemented in the lives of those with Settler inclinations. These rehearsals are designed to lessen tendencies toward dispossession and replace them with practices of de-possession, the exploration of a life lived in affinity with ongoing transfers and transitions of unbound matter rather than its monumental hoarding. While none of these rehearsals “solve the problem” of white supremacist neoliberalism, they permit practitioners to meaningfully engage with decoloniality in material, experiential, and intuitive ways and, with hope, encourage the emergence of a shared consciousness that turns away from dispossession and toward the circulation of care.